FIT MANUFACTURING: MAPPING PRODUCT COST REQUIREMENTS USING RELATIONAL DATABASE DESIGN - Ebrahim, Z.; Anawar, S.; Cheah, A.C.E (Journal of Advanced Manufacturing Technology (JAMT), 2015)
Efficiency of a manufacturing system depends on the capability of production to transform customer orders into products. Elimination of seven production wastes (i.e. defects, waiting, inventory, overproduction, transportation, motion, over-processing) is the concept used in Lean Manufacturing system to improve manufacturing efficiency. In this regard, the seven production wastes cause additional costs to the total product cost. Therefore, this paper aims to introduce a data model of product cost measurement system named as Product Cost System (PCS). The PCS will compute cost of a unit product that is important to the calculation of Production Waste Index (PWI). Thus, the concept of Relational Database Design has been applied in the development of PCS architecture. As the PWI will be measured on a monthly basis, the PCS database has been designed for calculating cost of a unit product based on one month production period. In this regard, the PCS data model integrates production input (order) quantity with materials cost, packaging cost, and labor cost. However, this paper presents only the first part of PCS that focuses on material cost and packaging cost. For the second part of PCS, a system for determining labor cost per unit product will be developed which is named as Labor Cost System (LCS). Then, both parts of PCS will be integrated to determine the PWI. Result of the first part of PCS prototype shows that further improvement is required in the aspect of bugs and errors.